E-technology and Manufacturing Enterprise Competitiveness. - Ketikidis, Panayiotis H. (Journal of Manufacturing Technology Management.)
This e-book on 'e-Technology and Manufacturing Enterprise Competitiveness' mainly comprises of selected papers presented at the 3rd International Workshop on Supply Chain Management and Information Systems (SCMIS2005), hosted by the South East European Research Centre (SEERC) - a collaborative venture of the University of Sheffield (UK) and Thessaloniki's CITY Liberal Studies (Greece) - Affiliated Institution of the University of Sheffield, on July 6 - 8 2005, in Thessaloniki, Greece. Past research on aspects of e-Technology tends to be fragmented. In today's digital economy, practitioners o.